2017
DOI: 10.1159/000460504
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PD-L1 in Human Gastric Cancer Cells Inhibits Tumor Progression and Improves the Cytotoxic Sensitivity to CIK Therapy

Abstract: Background/Abstract: PD-L1 has been an important target of cancer immunotherapy. We have showed that in human gastric cancer tissues, over-expression of PD-L1 was significantly associated with cancer progression and patients’ postoperative prognoses. However, as of now, how PD-L1 regulates the biological function of gastric cancer cells still remains elusive. Methods: We constructed the stable PD-L1 knockdown expression gastric cancer cell lines by using RNAi method, and further investigated the changes of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 41 publications
7
70
0
Order By: Relevance
“…PD-L1 is the major ligand and is expressed on a variety of cell types, importantly including many tumors such as lung cancer. Previous studies have reported that the PD-1/PD-L1 system is involved in tumor immunity and is closely associated with tumorigenesis and invasiveness [28-31]. Increased expression of PD-L1 is significantly associated with poor prognosis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is the major ligand and is expressed on a variety of cell types, importantly including many tumors such as lung cancer. Previous studies have reported that the PD-1/PD-L1 system is involved in tumor immunity and is closely associated with tumorigenesis and invasiveness [28-31]. Increased expression of PD-L1 is significantly associated with poor prognosis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 can be combined with PD-L1 and PD-L2 to inhibit the tumor microenvironment, tumor-specific T cell function, and immune surveillance function and promote tumor cell growth. 55,56 De Guillebon et al 57 evaluated the efficacy and safety of the PD-1 monoclonal antibody pembrolizumab for the treatment of advanced gastric cancer. The results showed that the response rate was 33%, the median response duration was 24 weeks, the 6-month PFS rate was 24%, and the 6-month OS rate was 69%.…”
Section: Immunotherapymentioning
confidence: 99%
“…Cells in which the nucleus was stained with fluorescein-dUTP were defined as TUNEL positive. The slides were then measured under a confocal microscope [28].…”
Section: Mitochondrial Membrane Potential (δψM) Atp Production and Mmentioning
confidence: 99%